THE CONTRIBUTION OF SHARIA REGIONAL REGULATIONS POLICY IN INDONESIAN LEGAL SYSTEM AS AN ALTERNATIVE FOR CHARACTER BUILDING IN THE COMMUNITY - Malihatul Azizah; Muntaha Mahfud; Abdul Basit (International Journal of Social Science, 2022)
The importance of morality in character building is linked to human life, questioning why people have to do good deeds, conduct excellent demeanor, and avoid misconduct. Indirectly, this question implies human morality, which desired the highest goodness and virtue in human life. Consequently, forming noble character and demeanor that becomes the purpose of education must have striven together within family, school, or society. This paper wants to determine whether the contribution of Sharia Regional Policy within the Indonesian Legal system as an Alternative of Character Building in the Community. The contribution of Sharia regional regulation implementation in Bulukumba and Indramayu, with a positive result, occurred on regional sharia regulation in Bulukumba, that is, positive acceptance from the Muslim and Non-Muslim communities with various efforts carried out by the local government. They strive extensively by establishing a successful team to monitor, evaluate, and measure the success of regional sharia laws and then, it is then linked to the decrement of criminality and the increment of social norms. The existence of Diniyah Madrasah (MDTA) is the policy taken by the local government to establish the nation's next generation into pious Muslim characters who have faith and piety. The second strategy is to prepare a religious and strong characterized generation and requires attaching a diploma to enter the SMP-MTs level by allocating 14 billion rupiah funds from the Regional Budget (APBD), including improving MDTA teachers quality. Third, the government set the criteria of ideal and standard for every MDTA to ensure they prepare the students comprehensively heading to the next educational level. The fourth strategy is to increase quality and educational relevance measures by achieving higher academic and non-academic skills that enable graduates to be proactive towards societal changes in various fields at the local, national and global levels. Increasing educational relevance and quality includes four aspects: curriculum, educational personnel, facilities and education, and leadership of the educational unit